The Soviet censorship - edited by Martin Dewhirst and Robert Farrell. (Scarecrow Press, 1973)
"[Issued] in cooperation with Radio Liberty Committee, New York, N.Y., and the Institute for the Study of the USSR, Munich, Germany."